WILLINGNESS TO PAY KONSUMEN TERHADAP PRODUK PERTANIAN ORGANIK (STUDI KASUS DI KODYA YOGYAKARTA) (THE CONSUMER'S WLLINGNESS TO PAY FOR ORGANIC PRODUCT) - Husodo, Sapto; Bharoto, Bharoto (Jurnal Ilmu-Ilmu Pertanian, 2009)
This research uses binary logistic regression model to estimate the probabilities of willingness to pay (IITP) of consumer for organic product as premium price. The data was collected through a consumer survey for the organic product purchasers at organic stores in Yogyakarta since October 2005 until January 2006. The model has one dependent variable namely WP as nominal binary variable and seventeen independent variables. Results suggest that 40 ok respondents are willing to pay for organic product. Results also indicate that respondents willing to pay a premium was affected by attitudinal factors, such as risk perception, environmental impacts, opinion on organic food labeling, perceived difference between organic and non-organic, and the potential benefits of organic foods.